Effect of Pythiumaphanidermatum Fungus, Quality of Irrigation Water and their Interaction in the Percentage of Seeds Germination and Spinach Content of Gibberellic acid(GA3) and Zeatin hormones - H.Kadhim, Jamal; H. Al-Ezerjawi, Nihad nihad.alez@gmail.com; N. Kamaluddin, Zahid (Al-Qadisiyah Journal of Pure Science, 2018)
The study results showed the superiority radial growth of the fungus Pythium aphanidermatum in distilled water treatment and the river water treatment where reported 4.50 and 4.48 cm respectively, compared to water drainage treatment, which was 4.06 cm . The results of the effect of interaction between the fungi and the quality of irrigation water in the percentage of germination of the spinach seeds and Weights of Gibberellic acid(GA3) hormone and Zeatin hormone to superiority of control treatment and the river water treatment, which amounted to 99.22% and 95.33 and 0.5120 micro gm/gm weight of seedling respectively significantly compared to all treatments, and that the highest percentage of death after seedling emergence was 100% in the P. aphanidermatum treatment and water drainage treatment significantly uperior on all Treatments. Notes from the results of the effect of fungus that control treatment (no fungus) increased significantly the percentage of seed germination and weights of Gibberellic acid(GA3) hormone and Zeatin hormone amounting 89.85% , 85.93 and 0.4302 micro gm/gm weight of seedling respectively, compared to the P.aphanidermatum treatment, which was 35.62% ,72.35 and 0.3486 micro gm/gm weight of seedling respectively and in the order,While appeared a higher percentage of death after seedling emergence in the P. aphanidermatum treatment amounting 92.82% significantly superior compared to the control treatment (nofungus), which was 7.89%.This tudy showed the effect of the quality of irrigation water to nthe river water treatment worked to a significant increase in the percentage of seeds germination and weights of Gibberellic acid(GA3) hormone and Zeatin hormone amounting73.21% , 89.21 and 0.4574 micro/gm weigh tof seedling respectively compared to the water drainage treatment, which were 52.25% , 69.07and 0.3214 microgm weight of seedling respectively and in the order,The study also showed that water drainage treatment has worked to increase the percentage of the death after seedling emergence amounting 56.66% compared to the river water treatment, which was 44.04%.